Synthesis, single crystal X-ray, DFT, spectroscopic, molecular docking studies and in vitro biological evaluation of compound N-benzyl-4-(4-chlorophenyl)-2-oxobutanamide - Das B.; Baidya A.T.; Devi B.; Rom T.; Paul A.K.; Thakur B.; Darreh-Shori T.; Kumar R. (My University, 2025)
Several α-ketoamides from natural as well as synthetic sources have been shown to possess multitude of biological activities due to their versatile nature and presence of multiple reactive centres giving them both electrophilic and nucleophilic characters. This makes them a key scaffold in chemistry and chemical biology. In this paper, we have reported the synthesis of N-benzyl-4-(4-chlorophenyl)-2-oxobutanamide (1) from β,γ-unsaturated α-hydroxythioester. Single crystal X-ray diffraction study was performed to determine the three-dimensional (3D) structure of the compound 1. Further, the 3D structure was optimised through DFT calculations using B3LYP/6-311G(d,p) basis set, followed by FTIR and NMR spectra calculation. The wavelength of maximum absorbance (λ) and the band gap energy of compound 1 were derived for methanol using the TD-DFT/6-311G(d,p) approach and compared to experimental results. The different intermolecular and intramolecular interactions such as H-O, H-Cl, H-C, H-N, and other possible interactions in the crystal structure were explored using Hirsfeld surfaces analysis and fingerprint plots. Additionally, Coulomb energy, dispersion energy, total energy, and total energy annotated were calculated by energy framework calculations demonstrating that electrostatic and repulsion forces are relevant to the topology of the overall interaction energies in the crystal. Finally, from the DFT optimized structure, the molecular electrostatic potential (MEP) map and Mulliken charges were generated and the natural bond (NBO) analysis was performed in order to investigate the interaction between various orbital and lone pairs occurring within the compounds. Based on the geometric and spectroscopic parameters, the experimental and theoretical results were indistinguishable. Additionally, in vitro amyloid beta 1-42 (Aβ42) aggregation assay revealed that the compound 1 modulated the aggregation profile of Aβ42 and the MTT cellular cytotoxicity assay showed that the compound is not toxic to cells. Further, molecular docking study resulted in the determination of interaction of compound 1 with the Aβ42 fibrils. In summary, the present work can be helpful for the design, and synthesis of novel α-ketoamides as potential modulators of amyloid beta aggregation. © 2022